Understanding the Factors Contributing to Pressured Ice in the Hudson Strait, Canada: An Interdisciplinary Analysis of Winter Ship Besetments - Ogilvie, Annika (Université d'Ottawa / University of Ottawa, 2019)
Ice strengthened vessels travelling through Arctic waters can have extreme difficulty passing through areas of ice pressure. Pressured ice and ice ridges can cause ships to become stuck, or beset, introducing additional environmental and economic costs. Understanding where and when ridges are forming along a shipping route would allow for better planning of safe winter navigation through ice-covered waters, however, there are many dynamics involved in the formation of pressure ridges that makes forecasting them with accuracy, in a specific geographic region, incredibly difficult. Winter shipping operations, in the Hudson Strait, Canada, are often impacted by pressured ice and ridges, sometimes causing ships to be delayed for several days at a time. Meteorological data is used in this thesis study to 1) to determine if land based meteorological data from weather stations can be used as a proxy for weather conditions experienced by ships in the marine areas where pressured ice and ridges are common, and 2) better understand the possible climatic factors that influence the besetment of ships in pressured ice in the Hudson Strait. This study is completed using information from ship logbooks detailing the difficult ice conditions encountered by ships transiting through the Hudson Strait in the winter months, and compares meteorological data from a land based station in Salluit, QC to meteorological data recorded on a ship, nearby, in the Hudson Strait.